The Values of Character Education in the Tradition of The Batu Urip Community - Drajat Friansah; Dwi Yanti; Sarkowi Sarkowi (STAI Hubbulwathan Duri, 2023)
This study aims to explore the cultural character values contained in the potential of Batu Urip. This study used a qualitative descriptive method with data sources in the form of a literature review, observation, and interviews. Data analysis techniques used in this study include transcripts of interview results, data reduction, analysis, data interpretation and triangulation from the results of data analysis, which are then concluded. The technique used in selecting the sample is non-probability sampling by means of purposive sampling, while the correspondents from this study amounted to 2 people who were traditional stakeholders and local youth leaders from Batu Urip. The results of this study were 3 potentials that contain the values of cultural characters in Batu Urip, namely: 1) Kasai Bathing with the character values of cooperation, responsibility, religion, and love for the homeland 2) Sedekah Rami with Values of the characters contained in the rami alms ceremony are religious, democratic, disciplined, social care, tolerance, love for the homeland, and the spirit of nationalism, and 3) Nnyoknyen traditional games with religious character values, independent, responsible, peace-loving, hard work, honest, democratic, and disciplined, and love the homeland.